Analyzing the relationship between electrification, non-agricultural entrepreneurship and household income in Togo - Kuamvi Sodji; Kassimou Gountante; Komla Senyo Konou; Bonaventure Sandabalo Katale; Kofi Houesse (Cogent Economics & Finance)
For the Togolese authorities, access to electricity for a large segment of the population is supposed to encourage entrepreneurship and pave the way for Togo’s modernization and development. This article examines the link between access to electricity, non-agricultural entrepreneurship and household income in Togo. The propensity score method, the endogenous treatment regression model and data from the harmonized household living conditions survey show that access to electricity has a beneficial impact on a household’s decision to run a non-agricultural business. Also, the probability of trading is 92.1% higher among households running non-agricultural businesses when they have access to electricity. Initiatives to promote access to electricity can play a crucial role in the growth of entrepreneurship and the transformation of the non-agricultural sector in Togo. Policies and programs to promote non-agricultural entrepreneurship should be combined with initiatives to improve access to electricity and the development of entrepreneurial capacities, thus contributing to poverty reduction.